2018
DOI: 10.1007/s12034-018-1622-2
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced properties of UPE/ESOA partially bio-nanocomposites reinforced with chitosan functionalized graphene nanoplatelets: an innovative approach

Abstract: The current study deals with the successful development of chitosan-functionalized graphene nanoplatelets (CS/GNPs) and their dispersion in the unsaturated polyester (UPE)/epoxidized soybean oil acrylate (ESOA) (80:20 w/w) blend system in different compositions of 0.3, 0.5 and 0.7 wt%. The resulting nanocomposite mixture was achieved by simple sonication method and pressed into a mould for fabrication of nanocomposite. The whole functionalization and nanocomposite preparation procedure were successfully tracke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Again an intense peak of ZnO at 440 cm −1 attributed to the stretching of Zn−O bonds. As FTIR analysis of chitosan has been done previously by the author so directly chitosan functionalization of ZnO was performed here [24] . Spectral study of CS‐ZnO is shown in Figure 3(b) which ascribed some new peaks for the stretching vibration of amine and hydroxyl groups at approximately 3400 cm −1 .…”
Section: Resultsmentioning
confidence: 99%
“…Again an intense peak of ZnO at 440 cm −1 attributed to the stretching of Zn−O bonds. As FTIR analysis of chitosan has been done previously by the author so directly chitosan functionalization of ZnO was performed here [24] . Spectral study of CS‐ZnO is shown in Figure 3(b) which ascribed some new peaks for the stretching vibration of amine and hydroxyl groups at approximately 3400 cm −1 .…”
Section: Resultsmentioning
confidence: 99%
“…Aside from the nanocomposites previously discussed, there are many other biodegradable and biocompatible nanocomposites used to enhance electronic conductors, which will not be carefully discussed here [174,175,176,177,178,179,180].…”
Section: Applications Of Nanocomposites For Electronicsmentioning
confidence: 99%